Causality between tourism and economic growth nexus. Issue 1 (2nd January 2022) - Wu, Tsung-Pao; Wu, Hung-Che; Wu, Yu-Yu; Liu, Ya-Tian; Wu, Su-Tsung
ABSTRACT: The purpose of this paper is to use a multivariate wavelet approach to examine the causal relationship between tourism and economic growth in the 11 Asian regions for the period from 1995 to 2016. Results indicate from the time-domain view, we show strong evidence linkages among the real international tourism receipts, international tourist arrivals, capital formation and real gross domestic product variables. From the frequency-domain view, we uncover significant wavelet coherency and strong relationships which change over time, indicating low to high frequency cycles. Accordingly, it can be recommended that the government needs to increase and promote tourism demand and to further provide and nurture the expansion of tourism supply.